ChemInform Abstract: Intrinsic Single‐Band Upconversion Emission in Colloidal Yb/Er(Tm):Na3Zr(Hf)F7 Nanocrystals. Issue 5 (13th February 2013) - Chen, Daqin; Lei, Lei; Zhang, Rui; Yang, Anping; Xu, Ju; Wang, Yuansheng
Abstract Lanthanoid‐doped Na3Zr(Hf)F7 nanocrystals are prepared solvothermally from EtOH solutions containing MOCl2 (M: Zr, Hf), Ln(NO3)3 (Ln: La—Lu), NH4F, sodium oleate, oleic acid, oleylamine, and H2O (autoclave, 130 °C, 12 h).